Flats for Foreigner After the Issuance of the Omnibus Law in Indonesia - Fauzan, Galang (NORMA, 2021)
This research is normative juridical research that uses a statutory approach. The government has issued its latest policy, namely, law number 11, the year 2020, concerning omnibus law, which regulates foreigner property rights regarding flats. Based on this regulation, a foreigner can have ownership rights over the flats. However, it results in problems because a nationality principle is regulated in Indonesian Land Law, prohibiting foreigners from having ownership rights. In Minister of agricultural regulation held that foreigners can only own flats unit based on usage rights. The result of this study, a foreigner, can have an apartment through the transfer of ownership such as buying and selling, grants, auctions, and so on, but it is only a right to use, not an ownership right. Foreigners who wish to own an apartment unit must meet the requirements and restrictions to maintain and prioritize Indonesian citizens’ interests.Keywords: Flats, Foreigner, Omnibus Law.